Microbial community and metagenome dynamics during biodegradation of dispersed oil reveals potential key-players in cold Norwegian seawater. Issue 1 (April 2018) - Ribicic, Deni; Netzer, Roman; Hazen, Terry C.; Techtmann, Stephen M.; Drabløs, Finn; Brakstad, Odd Gunnar
Abstract: Oil biodegradation as a weathering process has been extensively investigated over the years, especially after the Deepwater Horizon blowout. In this study, we performed microcosm experiments at 5 °C with chemically dispersed oil in non-amended seawater. We link biodegradation processes with microbial community and metagenome dynamics and explain the succession based on substrate specialization. Reconstructed genomes and 16S rRNA gene analysis revealed that Bermanella and Zhongshania were the main contributors to initial n -alkane breakdown, while subsequent abundances of Colwellia and microorganisms closely related to Porticoccaceae were involved in secondary n ‑alkane breakdown and beta‑oxidation. Cycloclasticus, Porticoccaceae and Spongiiabcteraceae were associated with degradation of mono- and poly-cyclic aromatics. Successional pattern of genes coding for hydrocarbon degrading enzymes at metagenome level, and reconstructed genomic content, revealed a high differentiation of bacteria involved in hydrocarbon biodegradation. A cooperation among oil degrading microorganisms is thus needed for the complete substrate transformation. Graphical abstract: Highlights: Biodegradation experiment in cold Norwegian seawater. Microbial community and metagenome succession correlate to hydrocarbon dynamics. Reconstructed genomes show narrow substrate specificity. Cooperation among hydrocarbon degraders is needed for complete substrate transformation.